Mentha longifolia lowers blood pressure in anesthetized rats through multiple pathways - Shah, Abdul Jabbar; Bukhari, Ishfaq Ali; Gilani, Anwarul Hassan (Bangladesh Journal of Pharmacology, 2016)
This study was aimed to investigate the effect of the extract of Mentha longifolia on blood pressure and the possible mechanisms. In anesthetized rats, the crude extract of M. longifolia and aqueous and chloroform fractions caused a dose-dependent fall in mean arterial pressure. Atropine pretreatment abolished the effect of extract and aqueous fraction but did not change that of chloroform fraction. In rabbit aortic rings, crude extract relaxed phenylephrine (1 µM) and high K+ (80 mM) pre-contractions. Chloroform fraction was more potent against high K+, similar to verapamil and caused a rightward shift in the Ca++ concentration-response curves. Aqueous fraction partially relaxed high K+ pre-contractions. In rat aortic rings, crude extract and aqueous fraction-induced endothelium-dependent atropine-sensitive vasodilator effect. Extract and fractions also relaxed high K+ precontractions. In guinea-pig atrial strips, crude extract and chloroform fraction suppressed force and rate of contractions, similar to verapamil. In conclusion, M. longifolia lowers blood pressure through Ca++ channel blockade and atropine-sensitive-NO pathway. Video Clip of Methodology: Experiment using aorta: 2 min 35 sec Full Screen Alternative